Increasing VO2 Max Through Circuit Training for Extracurricular Football Students at SMA Negeri 5 Soppeng - Akbar, Ilham; Hakim, Hikmad; Sahabuddin, Sahabuddin (Sains Global Institut, Indonesia, 2023)
This research aims to determine the effect of circuit training on increasing VO2 Max in extracurricular football students at SMA Negeri 5 Soppeng. The population of this study were all students of SMA Negeri 5 Soppeng with a research sample of 20 students selected as a total population and a group division system using ordinal maching. The data analysis techniques used are descriptive, data normality tests, homogeneity tests and t-tests using the SPSS program. The research results show that; There is an influence of circuit training on increasing VO2 Max in extracurricular football students at SMA Negeri 5 Soppeng. Increase in VO2 Max in extracurricular football students at SMA Negeri 5 Soppeng with an increase from an average score of 30.2500 to 44.3100.